Applying coordinate fixed Denavit–Hartenberg method to solve the workspace of drilling robot arm. (13th August 2018) - Ding, Feng; Liu, Cong
Drilling robot is a piece of large rock drilling equipment that integrates mechanical, electrical, and hydraulic technique, and it is a significant device for drilling and blasting. The drilling robot arm is the core component of the robot. To get intuitive and accurate modeling method to overcome the problem of the classic Denavit–Hartenberg method, for instance, the model mismatches the entity. The coordinate system fixed on the entity of Denavit–Hartenberg notation that is named coordinate-fixed Denavit–Hartenberg is creatively presented. The coordinate-fixed Denavit–Hartenberg method not only improves the accuracy and operability of kinematic analysis but also solves the workspace of drilling robot arm effectively. The drilling robot from an intelligent technology company in China is taken as the research example in this article. The homogeneous coordinate transformation matrix of each link rod is established through reasonably simplifying drilling robot arm as a multijoint structure. The coordinate-fixed Denavit–Hartenberg method is utilized for the first time in determining and verifying the kinematics equation of drilling robot arm. The kinematics equation is employed to obtain the effective workspace of drilling robot arm. The analysis results demonstrate that the design of drilling robot arm reaches the need of workspace in the actual structure as well as meets the functional requirements of drilling robot.